CoviHealth: A pilot study with teenagers in schools of Centre of Portugal - Villasana, María Vanessa; Pires, Ivan Miguel; Sá, Juliana; Garcia, Nuno M; Zdravevski, Eftim; CHorbev, Ivan; Lameski, Petre (Springer, Cham, 2020)
. Obesity is one of the most common problem that can be avoid with the correct education of the teenagers. There are different methods, but the use of the mobile devices to promote the creation of social challenges is important, because the teenagers act mainly in groups. The use of questionnaires, challenges and gamification purposes may promote the use of this type of mobile applications by teenagers. It is a special population that needs the adoption of different interactive technologies. The studies available are not validated by healthcare professionals. First of all, we started to analyze the related work of obesity problem, mobile applications, and different methodologies adopted with teenagers. By the end, seven students participated in the study with the performance of visualization of daily tips and curiosities, answering questionnaires, monitoring of physical activity and gamification. The teenagers were satisfied with the strategies adopted, but this study was affected by the pandemic situation around the world. In general, the participants were satisfied with the use of the mobile, and they would like to use it in the future for the improvement of their nutrition and physical activity habits.
Keywords: teenagers, mobile application, nutrition, physical activity, health, education